EVALUATION OF EXTRACURRICULAR PROGRAM MANAGEMENT SPORTS AT IMAM BUKHARI ISLAMIC BOARDING SCHOOL KARANGANYAR - Maryono, Adi; Soedjatmiko; hadi (Journal of Physical Education and Sports, 2024)
This research aims to: (1) Evaluate the management context of the sports extracurricular program at the Imam Bukhari Karanganyar Islamic Boarding School, (2) Evaluate the management input for the sports extracurricular program at the Imam Bukhari Karanganyar Islamic Boarding School. (3) Evaluate the sports extracurricular program management process at the Imam Bukhari Karanganyar Islamic Boarding School (4) Evaluate the sports extracurricular program management product at the Imam Bukhari Karanganyar Islamic Boarding School. This research is evaluation research with the CIPP method using a qualitative approach. The population of this research is administrators, coaches and extracurricular sports athletes at the Imam Bukhari Karanganyar Islamic Boarding School. Data collection techniques are observation, interviews, documentation and data triangulation. The data obtained was analyzed qualitatively with the following steps: (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of this research show that; (1) The management context of extracurricular sports programs at the Imam Bukhari Karanganyar Islamic Boarding School according to the management is good and the coaches are very good. (2) Management input for sports extracurricular programs at the Imam Bukhari Karanganyar Islamic Boarding School according to administrators, coaches and athletes is good. (3) The management process for sports extracurricular programs at the Imam Bukhari Karanganyar Islamic Boarding School according to the management is good, the coaches are very good, and the athletes are good (4) The management product for the sports extracurricular program at the Imam Bukhari Karanganyar Islamic Boarding School according to the management and coaches is good and the athletes are quite good Conclusions from this research; (1) The context of management programs extracurricular sports at the Imam Bukhari Karanganyar Islamic Boarding School is good. (2) The input of management programs sports extracurricular at the Imam Bukhari Karanganyar Islamic Boarding School is good. (3) The process of management program Sports extracurricular at Imam Bukhari Karanganyar Islamic Boarding School is good (4) The product of management program extracurricular Sports at Imam Bukhari Karanganyar Islamic Boarding School is quite good.